Mediating role of metacognitions in the relationship between cognitive avoidance and smoking addiction: a structural equation modeling - Mahmut Evli; Nuray Şimşek (Cukurova Medical Journal, 2021)
Purpose: Cognitive processes have an important place in starting or quitting smoking, which is an important public health problem all over the world. The present study was conducted to determine the mediator role of metacognition about smoking in the relation between cognitive avoidance and nicotine addiction in individuals who want to quit smoking. Materials and Methods: The study was completed with a total of 294 people who volunteered to participate in the study and who filled the data collection forms. In the evaluation of the data, descriptive statistics and the Spearman Correlation Test was used for correlation analysis. The effects of cognitive avoidance, nicotine addiction, and metacognition about smoking on each other was examined with structural equality modelling. Results: A total of 61.9% of the volunteers who participated in our study were male, and the mean age was 33.17±10.62. The data were found to support the model, and the goodness of fit indices were acceptable (CMIN/DF=2.02, GFI=0.93, AGFI=0.90, CFI=0.96, RMSEA=0.059). Cognitive avoidance and metacognitive beliefs affect nicotine addiction in individuals who want to quit smoking, and metacognitive processes about smoking played mediator roles in the interaction between cognitive avoidance and nicotine addiction. Conclusion: It will be useful to include cognitive processes as well as metacognitive processes about smoking in smoking cessation programs.